Hypoglycemic effect of C. butyricum-pMTL007-GLP-1 engineered probiotics on type 2 diabetes mellitus - Dexi Zhou; Shengjie Li; Gang Hu; Yufan Wang; Zhanghua Qi; Xuan Xu; Jing Wei; Qiong Liu; Tingtao Chen (Gut Microbes)
Diabetes mellitus (DM) is a complex metabolic disease characterized by hyperglycemia. Recently, the incidence of diabetes has increased exponentially, and it is estimated to become the seventh leading cause of global mortality by 2030. Glucagon-like peptide-1 (GLP-1), a hormone derived from the intestine, has been demonstrated to exert remarkable hypoglycemic effects. However, its limitation lies in its short plasma half-life, necessitating the continuous intravenous injection of GLP-1 drugs to achieve efficacy. Here, we engineered Clostridium butyricum to continuously express and deliver GLP-1 (denoted as Cb-GLP-1), and assessed its therapeutic efficacy in type 2 diabetes mellitus (T2DM) mice. We demonstrated that administration of Cb-GLP-1 effectively lowered blood glucose levels, regulated dyslipidemia, and ameliorated hepatic impairment in T2DM mice. Furthermore, Cb-GLP-1 treatment facilitated insulin secretion by retarding islet cell apoptosis and activating the glucagon-like peptide 1 receptor/adenylate cyclase/protein kinase A (GLP-1 R/AC/PKA) signaling pathway. Gut microbiota analysis revealed that Cb-GLP-1 restored gut homeostasis disrupted in T2DM mice, as indicated by the decreased abundance of Lactobacillus and Providencia genera in response to Cb-GLP-1 treatment. Collectively, the intestinal microbiota regulation and hypoglycemic effect of the engineered strain Cb-GLP-1 presents a promising approach for diabetes management.